A study on the efficacy and safety of combining dental surgery with tonsillectomy in pediatrics - Syed F; Uffman JC; Tumin D; Flaitz CM; Tobias JD; Raman VT (Dove Medical Press, 2018)
Faizaan Syed,1 Joshua C Uffman,1,2 Dmitry Tumin,1 Catherine M Flaitz,3,4 Joseph D Tobias,1,2 Vidya T Raman1,2 1Department of Anesthesiology & Pain Medicine, Nationwide Children’s Hospital, 2Department of Anesthesiology & Pain Medicine, The Ohio State University College of Medicine, 3Department of Dentistry, Nationwide Children’s Hospital, 4Division of Dentistry, The Ohio State University College of Dentistry, Columbus, OH, USA Purpose: Few data exist on combining pediatric surgical procedures under a single general anesthetic encounter (general anesthesia). We compared perioperative outcomes of combining dental surgical procedures with tonsillectomy during one anesthetic vs separate encounters. Methods: We classified elective tonsillectomy ± adenoidectomy and restorative dentistry as combined (group C) or separate (group S). Outcomes included anesthesia time, recovery duration, the need for overnight hospital stay, and postoperative complications. Results: Patients aged 4±1 years underwent tonsillectomy and dental surgery in combination (n=7) or separately (n=27). No differences were noted in total anesthesia time (C: median: 150, interquartile range [IQR]: 99, 165 vs S: median: 109, IQR: 92, 132; 95% CI of difference in median: –58, +10 minutes; P=0.115) and total recovery time (C: median: 54, IQR: 40, 108 vs S: median: 72, IQR: 58, 109; 95% CI of difference in median: –16, +48 minutes; P=0.307). The need for overnight stay (C: 4 of 7, S: 20 of 27; P=0.394) did not differ between the groups. No postoperative complications were noted in either group. Conclusion: These preliminary data support the potential feasibility of combining dental procedures with tonsillectomy during a single anesthetic encounter. Such care may not only reduce costs but also limit parental work absences and increase convenience for patient families. When compared with procedures performed separately, combined procedures did not result in increased morbidity or significant changes in postoperative outcomes.Keywords: combined, separate, tonsillectomy, adenoidectomy, dental, surgery, anesthesia